Implementation of Discovery Learning Models on Learning Outcomes of Islamic Religious Education at SMA Negeri 4 Bekasi City - Wahyuningsih, Irma Beni; Suharyat, Yayat; Hasibun, Akmal Gunawan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The he quality and success of learning is influenced by the competency and accuracy of the teacher in choosing and using the learning model. The learning model is a plan or a pattern that is used as a guide in planning teaching and learning activities. The teacher can choose a learning model that suits the characteristics of the students. This study aims to determine the implementation of PAI lessons using the Discovery Learning learning model at SMA Negeri 4 Bekasi City, and to explain the constraints and supports for implementing the discovery learning model in improving student learning outcomes at SMA Negeri 4 Bekasi and how the PAI learning outcomes after using the discovery learning model. The research method used is a qualitative method with a descriptive approach by conducting interviews to gather information. The subjects of this study were high school level students. The results of the study explain that when the learning process in class takes place the teacher's role is as a guide and then assesses student learning outcomes. The discovery learning model is a form of various models that are widely used by educators in the teaching and learning process so that learning objectives are achieved in accordance with learning objectives.